Lernaea cyprinacea (Copepoda: Lernaeidae) in Piabarchus stramineus (Characiformes: Characidae) from the Taquari River, São Paulo State, Brazil - Narciso, Rodrigo Bravin [UNESP]; Acosta, Aline Angelina [UNESP]; Nobile, André Batista [UNESP]; de Lima, Felipe Pontieri [UNESP]; Freitas-Souza, Diogo [UNESP]; da Silva, Reinaldo José [UNESP] (Springer Nature, 2019)
Lernaea cyprinacea is a lernaeid copepod also known as anchor worm. This species is considered one of the most invasive ectoparasites on fishes, with a worldwide distribution. In Brazil, L. cyprinacea has spread in almost the entire country, being recorded parasitizing both native and farmed fishes. Post-metamorphic adult females of L. cyprinacea were recorded for the first-time parasitizing larvae and juveniles of the native fish Piabarchus stramineus sampled in the Taquari River, Upper Paranapanema River, São Paulo State, Brazil. The lernaeids were found attached to the base of the fins, with a preference for the pelvic fin (43.7% of parasitized hosts). The presence of these parasites on larvae/juveniles resulted in deformations in the host bodies and modification of the caudal peduncle angulation. The findings of L. cyprinacea infecting P. stramineus raises concern about the dispersal of this invasive parasite in natural areas and the deleterious effects of this parasite, especially in young fishes.
Keywords: Anchor worm; Cyclopoida; Ectoparasite; Lernaeosis; Paranapanema; Taquari